Inactivation kinetics, structural, and morphological modification of mango soluble acid invertase by high pressure processing combined with mild temperatures. (March 2018) - Li, Renjie; Hou, Zhiqiang; Zou, Hui; Wang, Yongtao; Liao, Xiaojun
Abstract: The activity, structure and morphology of mango soluble acid invertase (SAI) were investigated after high pressure processing (HPP) combined with mild temperature at 50–600 MPa and 40–50 °C. The activity of mango SAI was efficiently reduced by HPP at 50 MPa/45 and 50 °C, or 600 MPa/40, 45 and 50 °C, while it was increased by 10–30% after HPP at 50–200 MPa/40 °C. Significant antagonistic effect of pressure and temperature on the activity of SAI was observed at 50–400 MPa/50 °C. The secondary structure of SAI was not influenced by HPP. However, its tertiary structure was modified by HPP, and severer modification occurred with higher pressure, higher temperature, and longer treatment time. Results of atomic force microscope suggested that HPP at 400 MPa/50 °C for 2.5 min induced dissociation of SAI, and HPP at 600 MPa/50 °C for 30 min resulted aggregation of SAI. Graphical abstract: Highlights: HPP combined with mild temperatures inactivate mango soluble acid invertase (SAI). HPP at 400 MPa/50 °C for 2.5 min induced dissociation of mango SAI. HPP at 600 MPa/50 °C for 30 min induced aggregation of mango SAI.